El Paleolítico en la actual provincia de León: revisión histórica - Neira Campos, Ana (Estudios humanísticos. Geografía, historia y arte, 1991)
This paper presents a revision of paleolithic research history in the province of Leon, from the firts scholars up to present time. Afterwards, it offers a brief state of current research in this province, showing their relationships with near geographic areas.